Spectrophotometric Method for Simultaneous Estimation of Paracetamol and Piroxicam in Tablets - SHIRKHEDKAR, A.A.; SHAIKH, AFSAR; SURANA, S.J. (Asian Journal of Chemistry, 2010)
A simple, rapid, accurate and precise spectrophotometric method has been developed for simultaneous estimation of paracetamol and piroxicam from tablet dosage form. Method involves, formation of Q-absorbance equation at 257 nm (λmax of paracetamol) and 320 nm (isoabsorptive point) in 0.01 N NaOH. The linearity lies between 4-12 mcg/mL for paracetamol and 4-40 mcg/mL for piroxicam. The results of recovery studies confirm the accuracy of the proposed method.